Предмет: Алгебра,
автор: Евгений235
преобразуйте выражение в многочлен:а)(2а-1)^2;б)(х+3у)^2;в)(1/5х-у)(1/5х+у);
Ответы
Автор ответа:
0
а)(2а-1)²=(2a)²-2*2a*1+1²=4a²-4a+1
============================================================
б)(х+3у)^2==x²+2x*3y+(3y)²=x²+6xy+9y²
============================================================
в)(1/5х-у)(1/5х+у)=(1/5x)²-y²=1/25x²-y²
============================================================
============================================================
б)(х+3у)^2==x²+2x*3y+(3y)²=x²+6xy+9y²
============================================================
в)(1/5х-у)(1/5х+у)=(1/5x)²-y²=1/25x²-y²
============================================================
Автор ответа:
0
А откуда появилось 282 в первом выражении
Автор ответа:
0
это умножить)
Похожие вопросы
Предмет: Математика,
автор: kozellera666
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: kolobok6652
Предмет: Физика,
автор: temchik57
Предмет: Право,
автор: mantevewqt83